Effectiveness of Cognitive Behavioral Therapy for Insomnia on Sleep Quality in Patients with Insomnia: A Meta-Analysis - Cynthia Octaviani; Hanung Prasetya; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: The relationship between sleep quality and sleep quantity is very close and has a significant impact on a person's sleep needs. If someone does not get enough sleep, then this will have an impact on the quality of their sleep, and vice versa. Therefore, maintaining a good quality of sleep is very important to maintain a healthy body and improve quality of life. The aim of the study was to analyze the effect of cognitive behavior therapy for insomnia (CBT-I) on sleep quality in insomnia patients. Subjects and Method: This study is a meta-analysis with PICO. Population: insomnia patients. Intervention: given cognitive behavior therapy for insomnia (CBT-I). Comparison: not given cognitive behavior therapy for insomnia (CBT-I). Outcome: sleep quality. The articles used in this study were obtained from five databases, namely PubMed, Embase, Web of Science, ScienceDirect, and Google Scholar. The keywords used to search for articles use the medical subject heading (MeSH) term and the emtree of the keywords